Knowledge management of financial performance for tax amnesty policy. (March 2019) - Setyorini, Riski; Achmad Daengs, GS; Mahjudin,; Reni, Andi; Ermayanti Susilo, Dwi; Hidayat, Rahmat
Abstract: the objectives of this study is to analyze differences of financial performance before and after the enactment of tax amnesty on XYZ company. This study is done by employing quantitative approach. Financial performance is measured by liquidity through current ratio, profitability through return on assets ratio, leverage through debt to equity ratio. Data analysis technique employed is different test with paired t test. The findings of this study indicate that there are differences in financial performance seen from liquidity measured through current ratio, profitability through return on assets ratio, leverage through debt to equity ratio before and after the enactment of tax amnesty policy.